The influence of perceived of usefulness perceived ease of use and perceived security on repurchase intention - Veshallini, Ravindran (2023)
The objective of this article is to explore the impact of perceived usefulness, perceived ease of use, and perceived security on repurchase intention in the context of online shopping on e-commerce platforms. The study specifically focuses on consumers in the Klang Valley region, including both Malaysians and non-Malaysians. A total of 250 valid respondents participated in the research, providing input through an online questionnaire distributed via a Google Form link.